Marketing strategy analysis based on segmenting and targeting in hospital: A literature review - Abdulaziez Mufakhhir; Sutopo Patria Jati; Septo Pawelas Arso (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Healthcare services have undergone changes in several strategic business units that require proper management handling. The evolution of hospitals, accompanied by the high demands of the community for services, has led hospitals to compete in seeking new opportunities and strategies to meet consumer (patient) needs. In an effort to meet consumer expectations and desires, hospitals need to design a marketing mix that provides value to the target consumers. Management planning serves the target market based on hospital market segmentation.Purpose: To define the analysis of healthcare service market segments in a manner that supports the marketing process in hospitalsMethod: This study is a literature review. The research data sources were derived from literature obtained via the internet, including scientific research findings from various sources. The population in this study consisted of research focusing on the assessment of hospital market segmentation from 2015 to 2022. A total of 12 research articles were obtained from scholarly publications such as Science Direct, Scopus, ProQuest, Springer Link, Google Scholar, PubMed, JSTOR, and Emerald Insight. The collected data were then systematically analyzed.Results: This result revealed that a marketing strategy employing segmentation concepts, supported by an appropriate marketing mix, was an effective means to enhance healthcare services according to customer needsConclusion: This study concluded that hospital market segmentation analysis, based on geographic, demographic, psychographic, and behavioral factors and supported by an appropriate marketing mix, was an effective means to improve healthcare services according to customer needs.